The Implementation of Lesson Study in Initial Teacher's Education - Δάρρα, Μαρία (Education Sciences, 2020)
The main purpose of this paper is to investigate the perceptions of future teachers regarding the design of teaching through the implementation of the Lesson Study in the context of their initial education. The research was carried out during the spring semester of the academic year 2017-18 with the method of the anonymous written questionnaire that was completed by 112 students of the University of the Aegean, who attended the course "Analysis of the Didactic Field: Practical Exercises of First Phase ". The results of the research show that experience in lesson study motivate trainee teachers to achieve specific goals and improve their performance, because it enables them to analyze their lessons based on the learning objectives stated, to conduct detailed discussions on educational strategies such as the question techniques, the prediction of students’ responses, to assess the lesson plan, and to assess their attempt. Additionally, the most important advantages from the implementation of the lesson study are co-operation, professional development of trainee teachers, reflection, active learning that include constructive discussion, planning, practice, observation and feedback.